2010
DOI: 10.1210/jc.2009-2719
|View full text |Cite
|
Sign up to set email alerts
|

Association of Vascular Endothelial Growth Factor Polymorphisms with Nonproliferative and Proliferative Diabetic Retinopathy

Abstract: VEGF polymorphisms might be a useful predictive marker for the development and progression of DR at an earlier stage of diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 16 publications
2
35
0
Order By: Relevance
“…The meta-analysis showed that -634C/G polymorphism C allele and genotypes CC vs CG + GG and CG vs CC + GG had no statistically significant association with DR. The result further verified most former results [13][14][15][16][17][18][19][20][21] . Meta-analysis is a summary analysis method that can combine various similar research results.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…The meta-analysis showed that -634C/G polymorphism C allele and genotypes CC vs CG + GG and CG vs CC + GG had no statistically significant association with DR. The result further verified most former results [13][14][15][16][17][18][19][20][21] . Meta-analysis is a summary analysis method that can combine various similar research results.…”
Section: Discussionsupporting
confidence: 89%
“…Thus, VEGF5'-untranslated region-634C/G polymorphism is an independent risk factor in DR. However, further studies on the association yielded similar [9][10][11][12] and opposite results [13][14][15][16][17][18][19][20][21] . Even in one country without ethnic diversity, different results were obtained.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research by Freathy, et al (2006) in UK, Nakamura, et al (2009) in Japan, and Chun, et al (2010) in Korea results in insignificant risk factor of DR. [4][5][6] This study aims to support DR pathogenesis theory through the role of genetic factor of VEGF C(-634)G polymorphism gene on promoter region to induce DR. Specifically this study observed VEGF C(-634)G Balinese variances gene and VEGF levels for evaluating risk factor of DR.…”
Section: Introductionmentioning
confidence: 94%
“…To date, many studies have investigated the associations between polymorphisms in the VEGFA gene and DR. -634G/C (+405G/C or rs2010963) polymorphism in the 5′-untranslated region and-2578C/A (−2549I/D (in high linkage disequilibrium with -2578C/A) or rs699947) polymorphism in the promoter region of the VEGFA gene are most frequently investigated. However, the results have been inconsistent [5][6][7][8][9][10][11][12][13][14][15][16]. To date, three relevant meta-analyses [17][18][19] have published.…”
Section: Introductionmentioning
confidence: 99%